PENINGKATAN KOMPETENSI GURU BAHASA JAWA DI KABUPATEN MAGELANG MELALUI PELATIHAN MODEL PEMBELAJARAN BERDIFERENSIASI - Sukoyo, Joko; Kurniati, Endang; Utami, Esti Sudi; Mujimin, Mujimin (Universitas Mataram, 2024)
Implementing differentiated learning in Javanese language lessons faces many challenges in the field. The primary reason is that teachers do not yet understand the concept of differentiated learning. So far, teachers have been teaching using conventional methods without considering the psychological aspects of students, such as their learning styles and interests. This community service program aims to improve teachers' abilities in designing differentiated teaching modules and applying them in Javanese language learning. The methods used in this community service program include lectures, question-and-answer sessions, demonstrations, and assignments. Lectures and question-and-answer sessions are used to deliver theoretical material. Demonstrations are used for practical material. Assignments are used to deepen competence so that participants become more skilled in the taught material. At the end of the program, an evaluation is conducted to assess the program's success, deficiencies, or weaknesses, and the results are used for future activities. The community service program has been well implemented. This program has positively impacted Javanese language teachers who are members of the MGMP Javanese Language High School in Magelang Regency. The data is evidenced by a 46% increase in teacher competence in developing differentiated teaching modules and a 39% increase in their ability to map students.